2017
DOI: 10.1128/aac.00324-17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ceftaroline against Methicillin-Susceptible Staphylococcus aureus Exhibiting the Cefazolin High-Inoculum Effect in a Rat Model of Endocarditis

Abstract: Certain Staphylococcus aureus strains exhibit an inoculum effect (InE) with cefazolin (CFZ) that has been associated with therapeutic failures in highinoculum infections. We assessed the in vitro activities of ceftaroline (CPT), CFZ, and nafcillin (NAF) against 17 type A ␤-lactamase (␤la)-producing, methicillin-susceptible S. aureus (MSSA) strains, including the previously reported TX0117, which exhibits the CFZ InE, and its ␤la-cured derivative, TX0117c. Additionally, we determined the pharmacokinetics of CPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…In a therapeutic context, this means that the fate of an initial infection depends on the initial load of bacteria—while small infections are easily cleared even with no antibiotics, large infections are hazardous, even when antibiotics are administered at high doses. This phenomenon, known as the “inoculum effect” (IE), is well established in-vitro [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], as well as in-vivo in animal models and in human patients [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a therapeutic context, this means that the fate of an initial infection depends on the initial load of bacteria—while small infections are easily cleared even with no antibiotics, large infections are hazardous, even when antibiotics are administered at high doses. This phenomenon, known as the “inoculum effect” (IE), is well established in-vitro [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], as well as in-vivo in animal models and in human patients [ 11 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As early as the 1970s, a subset of MSSA isolates was noted to exhibit striking elevations in 1GC MICs when a greater than standard inoculum was used in susceptibility testing (15,16). This phenomenon, which affects 1GCs (including cefazolin and cephalexin) but not nafcillin/oxacillin, is referred to as the cephalosporin (or cefazolin) inoculum effect (CzIE) (17,18). In a recent study of Argentinian adults with MSSA bacteremia treated with 1GC, it was noted that CzIE was an independent predictor of 30-day all-cause mortality (9).…”
mentioning
confidence: 99%
“…It is assumed that clinical failures occur as a consequence of strains possessing the CzIE at a high bacterial burden at the site of infection. In a previously described experimental model of endocarditis in rats, an MSSA isolate positive for the CzIE was associated with significantly higher bacterial counts in vegetations when treated with cefazolin compared to those with nafcillin, ceftaroline, or daptomycin (12,13). Furthermore, prospective observational data on the use of cefazolin in patients with MSSA bacteremia where the presence of the CzIE was assessed demonstrated that CzIE-positive isolates were associated with a significant increase in therapeutic failure and mortality (14,15).…”
mentioning
confidence: 96%